SENTIMENT ANALYSIS ON PLN MOBILE APPLICATION USERS' OPINIONS TO IMPROVE THE QUALITY OF PLN MOBILE SERVICES - Febry Claudia Nabasa Siahaan; Nazaruddin; Beby Karina Fawzeea (RADJA PUBLIKA, 2024)
transmission and distribution of electric power. PT PLN always strives to improve service to customers by creating creative, reliable and high quality service products. PT. PLN also launched a customer service application, namely PLN Mobile, in 2016 to meet all customer needs and provide convenience and a different electricity service experience. The existence of the PLN Mobile service application is one of the transformations to provide the best service for customers. The existence of PLN Mobile will give rise to sentiment in society, so researchers propose research using sentiment analysis to find out consumer opinions about the PLN Mobile application. This research uses the Naive Bayes algorithm with the help of RapidMiner software. The first stage is crawling the data and then processing it with various attributes such as document cleaning, tokenization process, transform cases, stopwords removal and filtering. Next, Naive Bayes modeling will be carried out and tested to obtain accuracy values. The data processed was 1068 data and divided into 320 training data and 748 testing data. The Naive Bayes accuracy result is 70.28%.